Reformate-enriched gasoline-ethanol blends: Volatility criteria and azeotrope formation - Manal Amine; Ezis N. Awad; Y. Barakat (Egyptian Journal of Petroleum)
Four hydrocarbon-base gasolines (BG) were formulated from the local refinery streams; isomerate, reformate, and light naphtha. The formulations were enriched in reformate. Each of these BG formulations was blended with 10 vol% of anhydrous ethanol. From ASTM-D86 distillation data, eight distillation curves were constructed and the trend line equations of these distillation curves were developed. Also, the area under each distillation curve (AUDC) was calculated through calculus definite integration technique. Subsequently, the area due to azeotrope formation (ADAF) for each BG-ethanol blend was estimated. In this paper, the influence of increasing reformate proportions on the created positive azeotrope, was studied. Also the influence of increasing reformate proportions on vapor pressure, Temperature for the vapor-liquid ratio of 20, T50 and octane number was studied. The results show that the R2 values of the distillation curve equations prove the reliability of the fits. Also, increasing reformate proportion in the fuel blend improves the octane number while increasing reformate proportion decreases the volatility of the fuel formulation. Keywords: Gasoline-ethanol blend, Reformate, Area under distillation curve, Vapor pressure, T50, Research octane number